AN ANALYSIS OF TYPES AND CONTEXTS OF DIRECTIVE SPEECH ACTS IN HOWARD AND BUSH’S ENCANTO MOVIE - Putri, Rizki Rienda Solehati; Delfi, Syofia; Eliwarti, Eliwarti (Universitas PGRI Sumatera Barat, 2024)
The aspect of Directive Speech Acts can be analyzed through movie in order to find out how they are used in everyday situations. The result might be useful for learners whose first language is not English. In order to find out types and contexts of Directive Speech Acts in a movie, this research aims to analyze types and contexts of Directive Speech Acts used in Howard and Bush’s Encanto Movie. The research method is descriptive qualitative research. The instrument of this research is audio-visual material and script of Encanto movie. The data were analyzed by using thematic analysis. The analysis about types of Directive Speech Acts is based on Searle’s theory and the context of Directive Speech Acts is based on Dell Hymes’s theory called SPEAKING MODEL as the reason in all produced utterance. The results of analysis show there are 10 types of Directive Speech Acts found in this movie. The most dominant types are commanding (23 data), questioning (19 data), and ordering (16 data), meanwhile, the less dominant type is prohibiting (1 data). The finding about the contexts of Directive Speech Acts shows 8 aspects of context in this movie. As the implication of this study, English teachers are expected to attract students’ interest in watching movie for outside classroom activities in order to learn the appropriate use of directive speech acts.